Development of biodegradable Zn-Mn-Li and CaP coatings on Zn-Mn-Li alloys and cytocompatibility evaluation for bone graft - Qiang, Hui-Fen; Lv, Zhao-Yong; Hou, Cai-Yao; Luo, Xin; Li, Jun; Liu, Kun; Meng, Chun-Xiu; Du, Wan-Qing; Zhang, Yu-Jue; Chen, Xi-Meng; Liu, Feng-Zhen (Frontiers in Bioengineering and Biotechnology, 2022)
Zn-based alloys are considered as new kind of potential biodegradable implanted biomaterials recently. The difficulty of metal implanted biomaterials and bone tissue integration seriously affects the applications of metal implanted scaffolds in bone tissue related fields. Herein, we self-designed Zn0.8Mn and Zn0.8Mn0.1Li alloys and CaP coated Zn0.8Mn and Zn0.8Mn0.1Li alloys evaluated the degradation property, and cytocompatibility. The results demonstrated that the Zn0.8Mn0.1Li alloys had profoundly modified the degradation property, and cytocompatibility, but Zn0.8Mn0.1Li alloys had particular adverse effects on the surface morphology of osteoblasts. The results furtherly showed that the CaP coated Zn0.8Mn and Zn0.8Mn0.1Li alloys scaffold had better biocompatibility, which would further guarantee the biosafety of this new kind of biodegradable Zn-based alloys implants for future clinical applications.